THE PRODUCTION OF TEXTS IN DIDACTIC MATERIAL AND IN EVALUATIVE CONTEXT: CONSIDERATIONS ON THE DISCURSIVE ETHOS - Fossey, Marcela Franco; Mendoca, Marina Celia [UNESP] (Univ Estadual Campinas, Inst Estudos Linguagem, 2019)
This article proposes to discuss the presence of the notion of ethos in activities related to writing: writing prompts at university entrance exams, candidates' responses to them and writing activities in a didactic manual aimed at High School. More specifically, we seek to observe the productivity of the notion when it implicitly integrates the writing instructions in the stage of schooling that precedes higher education and when it underlies the linguistic-textual maneuvers operated by candidates in function of the writing guidelines present in the writing exam of the Unicamp entrance exam. The notion is not explicit in the voice of the authors of didactic material or of the examining board, but can contribute to the quality of textual production in these contexts, as the analyses of the texts produced by the candidates point out.
Keywords: discursive ethos; writing; High School